Social Attitudes of Belarusians Towards Integration: Between the European Union and the Eurasian Economic Union - Kabiak, Aleh; Andras, Iryna (Sociološki pregled, 2019)
The location of Belarus between the Russian Federation and the European Union placed before the Republic a clear choice between the East and the West. Currently in the integration processes, there is also a heavy skew towards Russia due to historic and economic reasons. Public opinion is in favour of integration primarily with Russia (75.1%), according to the republican opinion survey Belarus-2030 conducted by the Institute of Sociology of National Academy of Sciences of Belarus (Minsk) in 2014, and the majority of the Belarusian population does not seek to join Europe. Therefore, the present-day formula of governmental (foreign policy) and people’s (social attitudes of the population) geopolitics of Belarus would be independence but with brotherly Russia.
Keywords: social attitudes; integration; Belarus; Russia